2020
DOI: 10.3390/molecules25092239
|View full text |Cite
|
Sign up to set email alerts
|

Optical Identification of Middle Ear Infection

Abstract: Ear infection is one of the most commonly occurring inflammation diseases in the world, especially for children. Almost every child encounters at least one episode of ear infection before he/she reaches the age of seven. The typical treatment currently followed by physicians is visual inspection and antibiotic prescription. In most cases, a lack of improper treatment results in severe bacterial infection. Therefore, it is necessary to design and explore advanced practices for effective diagnosis. In this revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…As AMR problem worsens, there is a lack of ideal medications for otitis media treatment, and severe cases may result in hearing impairment. [6][7][8][9] To tackle this, researchers have been striving to develop novel antibiotic alternatives, such as zinc oxide nanoparticles (ZnO NPs), titanium dioxide nanoparticles (TiO 2 NPs), and antimicrobial peptides (AMPs). Each of these drugs has its own strengths in antibacterial properties, yet they also come with their own limitations.…”
Section: Introductionmentioning
confidence: 99%
“…As AMR problem worsens, there is a lack of ideal medications for otitis media treatment, and severe cases may result in hearing impairment. [6][7][8][9] To tackle this, researchers have been striving to develop novel antibiotic alternatives, such as zinc oxide nanoparticles (ZnO NPs), titanium dioxide nanoparticles (TiO 2 NPs), and antimicrobial peptides (AMPs). Each of these drugs has its own strengths in antibacterial properties, yet they also come with their own limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Several advanced techniques and devices have been developed that probe these aspects of OM-such as better effusion detection through acoustic reflectometry (Muderris et al, 2013), "shortwave" light (Carr et al, 2016) or terahertz light (Ji et al, 2016), or by tracking TM mobility precisely using vibrometry (Kim et al, 2019). A comprehensive review of devices that can assess the ear for OM can be found in literature (Locke et al, 2020;Prasad et al, 2020). While many of these non-invasive optical characterization methods exist, no single technique provides a comprehensive picture of the infection state, which can capture both the structural and biochemical changes of the tissue (e.g., inflammation of TM, fluid presence and composition, presence of a biofilm, etc.…”
Section: Introductionmentioning
confidence: 99%
“…1 Before the age of seven, almost every child will experience at least one episode of ear infection. 2 Streptococcus pneumoniae is the most prevalent bacterium pathogen. Other microorganisms that cause this type of inflammation of the middle ear include Haemophilus influenzae, Moraxella catarrhalis, and Pseudomonas aeruginosa.…”
Section: Introductionmentioning
confidence: 99%